Implementation of a Quality and Patient Safety Curriculum for Pathology Residency Training - Suneeti Sapatnekar MD, PhD; Ryan Demkowicz MD; Deborah J. Chute MD (Elsevier, 2021)
Quality and Patient Safety education for resident physicians is necessary to prepare them for independent practice and to meet accreditation requirements. Integrating such education into the residents' routine work can provide them with valuable practical experience, while advancing the institution's quality priorities. We committed to Quality and Patient Safety education for our pathology residents but found no published program that met their specific needs. To fill this gap in pathology residency education, we designed and implemented a new curriculum that spans the 4-year duration of residency training. Curriculum content was drawn from the pathology milestones, and educational strategies were based on the principles of adult learning. The curriculum was implemented in the 2018 to 19 academic year, and residents were assessed before and after their participation. The residents engaged in several Quality and Patient Safety activities and projects under faculty supervision, and improved their scores on objective assessments (Quality and Patient Safety quiz and in-service examination). Implementation was facilitated by a Quality and Patient Safety chief resident, and the recruitment of faculty with demonstrated Quality and Patient Safety interest. Our comprehensive Quality and Patient Safety curriculum is feasible to implement and can help pathology residents develop the knowledge and skills needed to lead quality initiatives. We believe that the curriculum framework is readily adaptable to other residency programs.